Women in solitary: inside South Africa's female resistance to apartheid - Naidoo, Shanthini (Routledge, 2022)
The legacy of trauma -- Finding the women -- The trial -- Joyce Sikhakhane-Rankin -- Shanthie Naidoo -- Rita Ndzanga -- Nondwe Mankahla -- 'Rooi Rus' Swanepoel -- Winnie Mandela -- Aftermath -- Latter days -- On healing.